2002
DOI: 10.1021/ja0276220
|View full text |Cite
|
Sign up to set email alerts
|

LNAzymes:  Incorporation of LNA-Type Monomers into DNAzymes Markedly Increases RNA Cleavage

Abstract: Incorporation of two alpha-L-LNA/LNA nucleotides into each of the two binding arms of a "10-23" DNAzyme has been accomplished and the RNA cleavage with these novel LNAzymes studied. In comparison with the unmodified DNAzyme, the LNAzymes show significantly improved cleavage of the phosphodiester backbone at the target nucleotide in a small RNA substrate (58n RNA) under single-turnover conditions. The LNAzymes show efficient multiple turnover. With the LNAzymes, efficient cleavage was accomplished also of a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 16 publications
6
108
0
Order By: Relevance
“…35,36 RNA cleavage. 16 In line with previous findings, Jacobsen et al reported efficient inhibition of HIV-1 expression by targeting LNAzymes to functionally selected binding sites, 15 whereas targeting of miRNAs by using LNAzymes has recently been reported by Maiti and co-workers. 17 RNA interference (RNAi) has been developed as a highly potent approach to knock down gene expression.…”
Section: Future Prospectssupporting
confidence: 76%
“…35,36 RNA cleavage. 16 In line with previous findings, Jacobsen et al reported efficient inhibition of HIV-1 expression by targeting LNAzymes to functionally selected binding sites, 15 whereas targeting of miRNAs by using LNAzymes has recently been reported by Maiti and co-workers. 17 RNA interference (RNAi) has been developed as a highly potent approach to knock down gene expression.…”
Section: Future Prospectssupporting
confidence: 76%
“…LNA nucleotides have previously been incorporated into helical regions and/or recognition arms of the 10-23 catalytic DNA and the hammerhead ribozyme in an attempt to improve the targeting of cellular and viral RNA sequences, resulting in sometimes dramatic effects upon structural stability and target affinity (Vester et al 2002;Christiansen et al 2007;Donini et al 2007). The purpose of the LNAribozyme substitutions reported here is quite different, as we intend to probe the catalytic mechanism rather than to enhance hybridization affinity.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of locked nucleic acid include increased thermal stability of duplexes toward complementary DNA or RNA, stability toward 3 ¶-exonucleolytic degradation, and greater solubility due to structural similarities to nucleic acids (30,31). Locked nucleic acid incorporation into DNAzymes, however, has been found to influence both catalytic activity under single turnover conditions (24,26) and biological potency (26,32). Because DNAzymes with an inverted nucleotide at the 3 ¶ end are catalytically more efficient compared with their locked nucleic acid -modified counterparts due to a faster product release rate (25,33), they are still highly recommended for usage.…”
Section: Stability Of Dnazyme Moleculesmentioning
confidence: 99%